Consequences Of Climate Change And Mitigation Measures For Global Sustainable Development. - Mangla, Chhavi; Kumar, Aditya; Sharma, Chetan; Gupta, Seema; Kumar, Satish (Journal of Neonatal Surgery, 2025)
The mother earth is facing consequential environmental snag with fast depleting natural resources and threat to most of the ecosystems. A large number of environment’s friend is showing concerns on overall change in climate of the planet. The general state of the world’s climate is referred as ‘Global Climate’. Climate change can be categorized into two kinds--natural climate change and anthropogenic climate change. The first reason of changing climate is increased green house gases (GHGs), cutting of trees and human projected activities, resulting in change in the form of increase in temperature, change in rainfall pattern, melting of glaciers and rise in sea level, occurrence of wildfires etc. [1]. Climate has a profound influence on life on earth. It affects landforms, soil types and biodiversity thereby becomes a serious global concern. However, there is a need of the hour to attenuate the effect of global climate change for sustainability. The mitigation define by Intergovernmental Panel on Climate Change (IPCC): “An anthropogenic intervention to reduce the sources or enhance the sinks of greenhouse gases”. However, remedial steps need to be taken in order to embark upon these climatic issues. To end these hazards, innovative solutions must be brought forward.